A multi-mineral intervention to improve disease-related and mechanistic biomarkers in ulcerative colitis patients: Results from a randomized trial - Muhammad N. Aslam; Danielle Kim Turgeon; Henry D. Appelman; Ryan Stidham; Shannon McClintock; Ron Allen; Gillian Moraga; Isabelle Harber; Kara J. Jencks; Molly M. McNeely; Ananda Sen; Karl J. Jepsen; et al. (PLoS ONE, 2025)
Introduction The long-term goal of our ongoing studies is to determine if, and to what extent, a multi-mineral product (Aquamin) could benefit individuals with ulcerative colitis (UC). As a step toward achieving that goal, we carried out a pilot 180-day biomarker trial (clinicaltrials.gov ID: NCT03869905) in patients with UC in remission or with mild disease. Approach A total of 28 subjects participated in the study. Each subject was randomly assigned to receive either Aquamin for 180 days or placebo for 90 days. At Day-90, placebo subjects crossed over to Aquamin for the final 90 days. At Day-0, -90 and -180, serum samples were analyzed for C-reactive protein (CRP), alkaline phosphatase (ALP), intestine-specific ALP (ALPI), and for biomarkers of bone turnover (osteocalcin, TRAP5b and bone-specific ALP [BALP]). Stool specimens were assessed for fecal calprotectin (fCAL) and colon biopsies were examined histologically by Geboes scoring at the same time points. Each subject underwent DEXA scanning (at Day-0 and Day-180 only). In addition, mass spectrometry-based proteomic assessment was performed using colon biopsies obtained at each time point. Results Subjects who received Aquamin for the complete 180-day period (a total of 12) demonstrated improvements in all biomarkers (CRP, fCAL, ALP, ALPI, and Geboes scoring); this was not observed in the placebo group (16 subjects). When cumulative pre-post differences were compared between the Aquamin and placebo groups, Aquamin treatment significantly decreased these differences (a 24% decrease as compared to a 38% increase with placebo, p = 0.0284). Subjects who received Aquamin for 90-days showed intermediary responses. Subjects receiving Aquamin for 180 days also demonstrated increases in bone mineral density (BMD) and bone mineral content (BMC), resulting in a statistically significant increase (7.3%, p = 0.0324) in the hip strength index over the treatment period. This was accompanied by increases in osteocalcin and TRAP5b and a decrease in BALP. The proteomic screen demonstrated upregulation of multiple gut barrier proteins, cell surface transporter molecules and certain proteins with anti-inflammatory potential in response to Aquamin. Aquamin treatment also led to downregulation of several proteins associated with the pro-inflammatory state. Conclusion The results presented here suggest that the use of a multi-mineral intervention improves disease-related biomarkers in patients with UC. These studies suggest the potential value of the mineral intervention as a low-cost, non-toxic adjuvant therapy for mild UC or for individuals with UC in remission.